2015
DOI: 10.22495/cocv12i3c5p3
|View full text |Cite
|
Sign up to set email alerts
|

Promoter ownership and corporate leverage: Evidence from Indian firms

Abstract: A higher level of debt may help in aligning the interests of managers and shareholders; however, managers may underestimate the resulting costs of bankruptcy. Moreover, notwithstanding the tax and other benefits of debt, literature shows that firms may have more debt in their capital structure than is appropriate. A higher level of leverage becomes detrimental by increasing the chances of financial distress and, consequently, the chances of bankruptcy. This study investigated relationships between changes in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
1
6
0
1
Order By: Relevance
“…Promoter ownership is also widely recognized as one of the important types of board ownership structure that can influence a firm's value. Gill, et al (2015) find that promoter ownership is often regarded as concentrated board ownership by relatives, family members, and friends. The findings of the same study reveal that promoter ownership often reduces a firm's leverage, as most of the shareholders in promoter ownership belong to the same relatives and family.…”
Section: Board Ownership Structure and Firm Valuementioning
confidence: 99%
“…Promoter ownership is also widely recognized as one of the important types of board ownership structure that can influence a firm's value. Gill, et al (2015) find that promoter ownership is often regarded as concentrated board ownership by relatives, family members, and friends. The findings of the same study reveal that promoter ownership often reduces a firm's leverage, as most of the shareholders in promoter ownership belong to the same relatives and family.…”
Section: Board Ownership Structure and Firm Valuementioning
confidence: 99%
“…The study found that promoter shareholding inversely linked and extensively changes the leverage decisions. The agency theory supports the promoters’ ownership that helps to reduce firms’ financial distress and debt burden by providing effective management affairs (Gill, Obradovich, & Mathur, 2015b; Kaur & Gill, 2008).…”
Section: Promoters Ownershipmentioning
confidence: 99%
“…The promoters are restricted from trading on equity that is a higher utilization of bonds, preferred stock, and other debt sources that is expected to maximize the shareholder wealth. (Alhazaimeh et al, 2014; Gill et al, 2015b). The outcome is validated by the agency theory, and the higher promoters’ concentration implies relied on minimizing the agency cost and enhance the firm’s value.…”
Section: Fixed Effects Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…leverage had a positive relationship with concentrated shareholding and had a negative relation with diffuseness of shareholding after controlling for profitability, risk, tangibility, growth, and size. Gill et al (2015) investigated the relationship between capital and promoters shareholding and predicted that managers may take debt to please the shareholders but the risk of bankruptcy is always there and concluded that a change in promoter ownership played a significant role in reducing debt. Tawiah et al (2014) found a strong relationship between promoter ownership structure and board composition and argued that high promoter concentration is a contributing factor for more promoters on the board of the companies.…”
Section: Literature Reviewmentioning
confidence: 99%